Perlindungan Hukum Hak Pemegang Saham Pada Pebubaran Perusahaan di Karenakan Pailit - Fahira Ayu Tri Isnawati; Siti Mahmudah (LPPM Universitas Ekasakti Padang, 2023)
The world economic developments this day have encouraged so many aspects for human life. Capital market as one of economic needed fulfill alternative have start to reach by all of society member. It is an important thing to the government as the highest market authority to give a legal certainty in order to protect its people. Investing in capital market with stock form is one of investment choice for most people which is give a financing solution for most of company in the country. Especially for a listed company in the capital market. But investing in the capital market with stock form not only give a profit opportunity but also have a risk such as bankruptcy. The purpose of this article is to seek and analyze the legal impact of the bankruptcy of listed company to the capital market investor, and legal protection for capital market investor due the bankruptcy of listed company reviewed by Indonesia bankruptcy. For further examine the problems in this,uses a juridical normatif and qualitative juridicial ,the result of this research show that: first, the impact of bankruptcy for investor is make the loss of capital gain opportunity which is caused by the stock lock up in the market by IDX and caused delisting for the stock of listed company. Second, the legal protection for investor due the bankruptcy of listed company is by the market trading system which is provided by the market disclosure principle and investor can reach the compensation by suing the company in the court.